2021
DOI: 10.3906/sag-2009-149
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen reserve index guided oxygen titration in one lung ventilation with low fresh gas flow

Abstract: Background/aim: Continuous oxygen reserve index (ORI) measurement with multiple wave pulse co-oximetry is a noninvasive measurement. The decrease in the ORI trend provides a prediction for the development of hypoxemia and provides information on hyperoxia. Our aim is to determine the effect of ORI-guided oxygen titration on hyperoxemia-mediated morbidity. Materials and methods:Consecutive 120 ASA I-III patients, 18-70 years of age, without severe obstruction or restriction, undergoing one lung ventilation (OLV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In another study investigating the effects of ORi-guided oxygen titration and hyperoxemia-mediated morbidity in one-lung ventilation, lower mean FiO 2 and PaO 2 values with ORi monitoring were reported. They concluded that in thoracic anesthesia, ORi-guided oxygen titration can protect from hyperoxia, reduce the length of hospital stay, and increase patient safety (24). In parallel with our study, these studies stated that ORi has a bene cial role in preventing hyperoxia and achieving optimum oxygenation with its guiding effect on FiO 2 titration.…”
Section: Changes Insupporting
confidence: 81%
“…In another study investigating the effects of ORi-guided oxygen titration and hyperoxemia-mediated morbidity in one-lung ventilation, lower mean FiO 2 and PaO 2 values with ORi monitoring were reported. They concluded that in thoracic anesthesia, ORi-guided oxygen titration can protect from hyperoxia, reduce the length of hospital stay, and increase patient safety (24). In parallel with our study, these studies stated that ORi has a bene cial role in preventing hyperoxia and achieving optimum oxygenation with its guiding effect on FiO 2 titration.…”
Section: Changes Insupporting
confidence: 81%
“…As a result, patients with ORi monitoring had lower PaO 2 values than patients without additional ORi monitoring. Saraçoğlu et al thus demonstrated that ORi monitoring could prevent the risk of hyperoxia in patients, and in this way shorten their postoperative stay in hospital [68].…”
Section: Ori In One-lung Ventilationmentioning
confidence: 98%
“…The usefulness of ORi monitoring was also studied during one-lung ventilation (OLV) in patients undergoing thoracic surgery [65][66][67][68][69]. Koishi et al demonstrated that there was a significant correlation between the ORi and PaO 2 during OLV.…”
Section: Ori In One-lung Ventilationmentioning
confidence: 99%